Designing the character profile of Pancasila through Islamic personal development activities in the late childhood phase - Ardi Satrial; Febrianto; Zulmasri; Nurhayati; Engkizar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This study aims to analyze the implementation of the Islamic Personal Development (IPD) program in fostering the character profile of Pancasila (CPP). The character of late childhood learners is still dynamic and responsive to environmental influences, so education is required for its development. One of the activities containing character education is the Islamic Personal Development program. This qualitative research uses a single case study design at non-government elementary schools in Bengkulu. The research data were collected through observations and interviews with the coordinator of Islamic Personal Development and class teachers. The data obtained were analyzed using the Miles and Huberman analysis model, including selecting data by the research objectives, presenting data in tables and narratives, and linking data and information with relevant research to find conclusions. This research found five character profiles of Pancasila in IPD activities organized in elementary schools, namely: i) the character of faith, devotion to God Almighty, ii) global diversity, iii) cooperation, iv) critical reasoning, and v) independence. Islamic Personal Development activities can be an option for the character profile of the Pancasila program in character development for late childhood learners.